Community based peer-led TB screening intervention: an innovative approach to increase TB knowledge, presumptive case identification, and referral among sexual minority people in urban Bangladesh - Golam Sarwar; Shaan Muberra Khan; Samira Dishti Irfan; Mohammad Niaz Morshed Khan; Md. Masud Reza; A K M Masud Rana; Rupali Sisir Banu; Shahriar Ahmed; Sayera Banu; Sharful Islam Khan (BMC, 2023)
Abstract Introduction One of the contributors to tuberculosis (TB) burden among vulnerable populations, such as sexual minority people, is the delay in case finding and notification. Given their socially excluded, hard-to-reach nature, community-led approaches need to be introduced to facilitate their screening of TB symptoms and their subsequent referral to TB healthcare providers. This article aimed to explore the existing challenges surrounding TB screening and referral, and the implementation facilitators and barriers of the proposed community-based TB screening model for sexual minority people in Dhaka, Bangladesh. Methods This study followed the quasi-experimental design using mixed methods (i.e., qualitative and quantitative) approach. The study participants who were also a part of the community-led TB screening model included sexual minority people enrolled in HIV prevention interventions. In addition to quantitative inquiry, in-depth interviews were conducted on sexual minority people, focus group discussions were also conducted on them and HIV prevention service providers, and key-informant interviews were conducted on service providers, programmatic experts and TB researchers. Data were analyzed using content, contextual and thematic approaches. Results The 'Six Steps in Quality Intervention Development' framework was used to guide the development of the community-based TB screening model. In Step 1 (identifying the problem), findings revealed low rates of TB screening among sexual minority people enrolled in the HIV prevention intervention. In Step 2 (identifying contextual factors for change), various individual, and programmatic factors were identified, which included low knowledge, low-risk perception, prioritization of HIV services over TB, and stigma and discrimination towards these populations. In Step 3 (deciding change mechanism), community-based screening approaches were applied, thus leading to Step 4 (delivery of change mechanism) which designed a community-based approach leveraging the peer educators of the HIV intervention. Step 5 (testing intervention) identified some barriers and ways forward for refining the intervention, such as home-based screening and use of social media. Step 6 (collecting evidence of effectiveness) revealed that the main strength was its ability to engage peer educators. Conclusion This study indicates that a community-based peer-led TB screening approach could enhance TB screening, presumptive TB case finding and referral among these populations. Therefore, this study recommends that this approach should be incorporated to complement the existing TB program.